«Thanks for remembrance about me»: letters of sainted hierarch Luke (Voyno-Ysenetsky) to priest Martin Rimsha the publication of hegumen Agathangelus (Dayneko) - Hegumen Agafangel (Daineko A.) (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The author brings to a scientific attention two unknown letters of bishop Luke (Voyno-Jasenetsky). The letters add remarkable characteristic traits to the image of the Sainted Hierarch and some new facts to known episodes of his biography. Letters covers the Tashkent period of bishop Luke’s life: the first letter was written on March, 10th, 1928 and the second letter — on July, 20th, 1929. To priest Martin Rimsha was addressed both letters. Sometimes this name appears in the literature about the Turuhansk period of the exile of Holy hierarch, however the addressee’s person is of interest, therefore the publication’s author represents his biographic data that have been restored according to archival documents. They are published for the first time. In the introduction the author describes the addressee’s biography, priest Martin Rimsha, and reports about his activity in the Turuhansky edge where remarkable church figures were in exile